Leukocytoclastic Vasculitis as the Presenting Symptom of Crohn's Disease in an Adolescent. (August 2020) - Ford, Vanessa; Mooney, Cassandra; Shah, Meera; Jenkins, Elan
Leukocytoclastic vasculitis (LCV) is a rare vascular inflammatory condition that affects post-capillary venules. Its incidence in the pediatric population is unknown. However, its incidence has been shown to increase with age. The causes of LCV can be varied, ranging from drugs to infections to systemic disease. LCV as a presenting symptom of inflammatory bowel disease (IBD) is rare, especially in the pediatric population. A 15-year-old female with a family history of systemic lupus erythematosus was transferred to our hospital with a month-long history of rash, joint swelling and tenderness, periorbital edema, weight loss, and diarrhea. She presented with the objective findings of a biopsy showing LCV and a computed tomography scan read that was concerning for IBD versus infectious colitis. She had a thorough workup, involving both the rheumatology and gastroenterology services, and was ultimately found to have Crohn's disease. This case reveals the importance of recognition of a constellation of symptoms in IBD even when they are not classical in nature at initial presentation.